Investigation on the Anticonvulsant Potential of Luteolin and Micronized Luteolin in Adult Zebrafish (Danio rerio) - Garbinato, Cristiane (2021)
Epilepsy affects around 50 million people worldwide, and an important number of patients (30%) fail to respond to any available antiepileptic drug. Previous studies have shown that luteolin presents a promising potential as an anticonvulsant. On the other hand, different studies showed that luteolin does not promote anticonvulsant effects. Therefore, there is a lack of consensus about the use of luteolin for seizure control. Luteolin low bioavailability could be a limiting factor to obtain better results. Attractively, micronization technology has been applied to improve flavonoids bioavailability. Thus, the present study aimed to investigate the effects of luteolin on its raw form and micronized luteolin in a PTZ-induced seizure model in adult zebrafish (Danio rerio). Our results demonstrate that luteolin and micronized luteolin did not block PTZ-induced seizures in adult zebrafish. Also, luteolin and micronized luteolin did not provoke behavioral changes. Finally, our results show that 24 h after seizure occurrence, no changes were detected for p70S6Kb, interleukin 1β, and caspase-3 transcript levels. Altogether, we failed to observe an anticonvulsant potential of luteolin in adult zebrafish, even in its micronized form. However, we recommend new studies to investigate luteolin benefits in epilepsy.